Microfluidic SAXS Study of Lamellar and Multilamellar Vesicle Phases of Linear Sodium Alkylbenzenesulfonate Surfactant with Intrinsic Isomeric Distribution - Poulos,AS; Nania,M; Lapham,P; Miller,RM; Smith,AJ; Tantawy,H; Caragay,J; Gummel,J; Ces,O; Robles,ESJ; Cabral,JT (Langmuir, 2016)
The structure and flow behavior of a concentrated aqueous solution (45 wt %) of the ubiquitous linear sodium alkylbenzenesulfonate (NaLAS) surfactant is investigated by microfluidic small-angle X-ray scattering (SAXS) at 70 °C. NaLAS is an intrinsically complex mixture of over 20 surfactant molecules, presenting coexisting micellar (L1) and lamellar (Lα) phases. Novel microfluidic devices were fabricated to ensure pressure and thermal resistance, ability to handle viscous fluids, and low SAXS background. Polarized light optical microscopy showed that the NaLAS solution exhibits wall slip in microchannels, with velocity profiles approaching plug flow. Microfluidic SAXS demonstrated the structural spatial heterogeneity of the system with a characteristic length scale of 50 nL. Using a statistical flow–SAXS analysis, we identified the micellar phase and multiple coexisting lamellar phases with a continuous distribution of d spacings between 37.5 and 39.5 Å. Additionally, we showed that the orientation of NaLAS lamellar phases is strongly affected by a single microfluidic constriction. The bilayers align parallel to the velocity field upon entering a constriction and perpendicular to it upon exiting. On the other hand, multilamellar vesicle phases are not affected under the same flow conditions. Our results demonstrate that despite the compositional complexity inherent to NaLAS, microfluidic SAXS can rigorously elucidate its structure and flow response.